2011
DOI: 10.1155/2011/247959
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of -Cell Replacement Therapy in Diabetes Mellitus: Islet Cell Transplantation

Abstract: Diabetes mellitus remains one of the leading causes of morbidity and mortality worldwide. According to the Centers for Disease Control and Prevention, approximately 23.6 million people in the United States are affected. Of these individuals, 5 to 10% have been diagnosed with Type 1 diabetes mellitus (T1DM), an autoimmune disease. Although it often appears in childhood, T1DM may manifest at any age, leading to significant morbidity and decreased quality of life. Since the 1960s, the surgical treatment for diabe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 283 publications
(274 reference statements)
0
19
0
2
Order By: Relevance
“…While exogenous insulin therapy remains the most common and effective standard for day-to-day control of Type 1 Diabetes (T1D), recurring incidences of hypoglycemic episodes and long-term complications such as retinopathy, neuropathy, nephropathy, and cerebrovascular/cardiovascular diseases necessitate transplantation of either whole pancreas or pancreatic islets as a more effective treatment in a high percentage of patients [1][2][3][4][5][6]. Of the two, clinical islet transplantation is less invasive, being associated with a 20% lower morbidity risk compared to whole pancreas transplantation.…”
Section: Editorialmentioning
confidence: 99%
“…While exogenous insulin therapy remains the most common and effective standard for day-to-day control of Type 1 Diabetes (T1D), recurring incidences of hypoglycemic episodes and long-term complications such as retinopathy, neuropathy, nephropathy, and cerebrovascular/cardiovascular diseases necessitate transplantation of either whole pancreas or pancreatic islets as a more effective treatment in a high percentage of patients [1][2][3][4][5][6]. Of the two, clinical islet transplantation is less invasive, being associated with a 20% lower morbidity risk compared to whole pancreas transplantation.…”
Section: Editorialmentioning
confidence: 99%
“…IAT candidates are counseled that exocrine deficiency may be made worse or induced by TP. Exocrine deficiency may be responsible for the more erratic blood sugar control in pancreatic diabetes than type 1 diabetes because of erratic absorption making the predicted insulin dose more difficult to calculate (Jahansouz et al, 2011;Robertson, 2010a;Robertson, 2010b). However, at least one group has reported that diabetic control after TP (for a variety of reasons) without IAT is equivalent to that of patients with type 1 diabetes in their clinic (Jethwa et al, 2006).…”
Section: Metabolic Considerationsmentioning
confidence: 99%
“…The largest series published to date on patients undergoing pancreatectomy and IAT have come from the University of Minnesota (Farney et al, 1991;Gores et al, 1992;Gruessner et al, 2004;Jie et al, 2005;Najarian et al, 1979;Najarian et al, 1980;Sutherland et al, 1978;Sutherland et al, 1980a;Sutherland et al, 2004a;Sutherland et al, 2009a;Sutherland et al, 2009b;Sutherland et al, 2011b;Wahoff et al, 1995a) (>400), the University of Cincinnati (Ahmad et al, 2005;Rodriguez et al, 2003;Sutton et al, 2010) (>100), the University of Leicester (Clayton et al, 2003;;Garcea et al, 2009;White SA et al, 1998;White SA et al, 2001;Webb et al, 2008) (>50 cases), but there are many center that are building their series (Argo et al, 2008;Berney T et al, 2000;Desai et al, 2011;Dixon et al, 2008;Jahansouz et al, 2011;Takita et al, 2010;Takita et al, 2011b;Valente et al, 1986) The reports from these centers largely focus on metabolic outcomes, QOL, and pain reduction., but there are many publications on specialized aspects of TP-IAT as have been referenced in this chapter.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations